Metode Pengajian Hadis Klasik Dan Kerangka Sistem Pendidikan Moden: Tinjauan Di Maahad- Maahad Tahfiz Selangor - Abu Zaki Ismail; Mohamad Fuad Ishak; Mohd Khafidz Soroni; Mohd Farid Ravi Abdullah; Syed Abdul Majid Ghouri; Mohd Norzi Nasir; Nurfida’iy Salahuddin (Hadis Research Institute, KUIS, 2024)
Hadith studies have stood by its own as a system before the existence of modern learning system. Various methods and approaches of study have been developed by the early generations including eight methods of taḥammul al-ḥadīth. For the purpose of adapting the hadith’s study in a modern system, this study reviews the methods of classical hadith studies, Islamic scholarly pedagogical theories and their practice in tahfiz schools in Selangor. Qualitative methods have been used in this research which includes analysis on classical method of education analysis and modern approaches, and interviews with nine chosen tahfiz schools in Selangor. The study also found that the hadith studies can be conducted in formal and non formal institutions in order to make the hadith studies more useful and comprehensive in the future.